Telaah Komprehensif Penyajian Materi Dan Teknik Evaluasi Buku Teks Bahasa Arab Kelas VIII Madrasah Tsanawiyah KMA Nomor 183 Terbitan Kemenag Tahun 2020 - Melly Cahyani; Asep Sunarko; Pamungkas Stiya Mulyani; Fatkhurrohman Fatkhurrohman (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2023)
The existence of books has a very important role in the learning process, as the saying goes that we are a window of knowledge that we can interpret that by reading books, we will get a lot of knowledge. This study aims to: 1) To find out how the suitability of the presentation of material in the textbook